Semantična prozodija Leksikalni in besedilno-diskurzivni vidiki - Šorli, Mojca (Lingua Slovenica, 2020)
The monograph focuses on corpus analysis of texts, exploring the interface between lexical and discursive aspects of pragmatic meaning. As the concept of evaluation is key to understanding how language works, our aim is to shed light on semantic prosody - a traditionally neglected evaluation-related phenomenon in Slovenian linguistics - as shown in some specific areas of applied linguistics, especially lexicography and translation. The locus of this phenomenon, which determines the pragmatic function of a unit of meaning, is in the textual, not the lexical meaning. This poses a challenge to modern lexicography. The introduction is followed by a brief outline of the history of pragmatic research and an analysis of selected lexical units, while in the second part of the book pragmatic aspects of textual and discursive analysis, including evaluation and metaphor, are presented. The importance of semantic prosody for linguistics is confirmed by tradition, as well as by insights in many areas closely related to language and interpretation of meaning, such as digitization and (language) technology, media discourse and policy, or law.